Effects of Different Astaxanthin Sources on Fillet Coloration and Energy Deposition in Rainbow Trout (Oncorhynchus mykiss) - Xiaoxue Meng; Fumei Yang; Lulu Zhu; Lingli Zhan; Toru Numasawa; Junming Deng (Aquaculture Nutrition)
A 9-week feeding trial was conducted to investigate the effects of different dietary sources of astaxanthin on fillet coloration, texture, and nutrient composition in rainbow trout (Oncorhynchus mykiss). Eight diets were formulated to contain 0, 25, 50, 75, 100, and 125 mg/kg astaxanthin from wall-broken Haematococcus pluvialis (WBHPA), 100 mg/kg astaxanthin from wall-unbroken H. pluvialis (WUHPA), or chemically synthesized astaxanthin (CSA). Each diet was fed to triplicate groups of rainbow trout (mean initial weight of 561 g) twice daily (07:00 and 17:00) to apparent satiation for 9 weeks. Results showed that at the 100 mg/kg astaxanthin inclusion level, the CAS group had higher fillet gross energy, dorsal fillet redness, and dorsal fillet color card score compared to the WBHPA-100 group, with both being higher than the WUHPA group (P<0.05). Fillet astaxanthin content, dorsal fillet yellowness, and lateral line redness and yellowness did not differ significantly between the CSA and WBHPA-100 groups (P>0.05), but were higher than the WUHPA group. When WBHPA was used, the inclusion of 50–100 mg/kg decreased fillet lightness but increased fillet redness, while better fillet texture was served at 75–125 mg/kg. Dietary 25–125 mg/kg WBHPA inclusion increased fillet astaxanthin and gross energy concentrations, with minor effects on fatty acid compositions of fillet. Inclusion of over 100 mg/kg astaxanthin regardless of source decreased fillet threonine and serine contents, and the WBHPA-100 group had lower fillet glycine and alanine contents compared to the control group (P<0.05). In conclusion, CSA had the most significant impact on fillet coloration and energy deposition in rainbow trout, while WUHPA had the least favorable effect. Additionally, the wall-breaking treatment of H. pluvialis can improve the effect of astaxanthin on fillet coloration and nutrient composition in rainbow trout, with a recommended dose range of 75–100 mg/kg.